Fracture network analysis of Yacoraite Formation in the Tres Cruces sub-basin, northwestern Argentina - Correa Luna, Clara (2019)
The Tres Cruces sub-basin, located in Jujuy province, northwestern Argentina, is characterized by intense N-S folding and faulting. These structures were formed as a result of the Cenozoic shortening that produced the tectonic inversion of the Salta Rift Basin normal faults. Some of the main folds and faults show abrupt trend variations, controlled by NW-SE transverse lineaments. We performed a fracture network analysis over the Maastrichtian-Danian limestones of the Yacoraite Formation, at three folds located in the central sector of the sub-basin. A total of 832 planar fractures were measured in different structural domains. Five main fracture sets were identified, trending NW-SE, NE-SW, ENE-WSW, WNW-ESE and N-S to NNW-SSE. Their relative chronology was established based on the observed abutting relationships. The analysis performed suggests that NW-SE, NE-SW and ENE-WSW trending sets are regionally represented and were formed before the initial stages of folding. Set ENE-WSW is sub-parallel to the convergence direction acting during the Neogene. The other two sets are associated with local perturbations of the far-field signal control by the oblique NW-SE lineaments. The origin of the WNW-ESE set remains unclear; its distribution is locally restricted to the San Bernardo domain. Finally, the N-S to NNW-SSE set shows a synfolding origin generated when the surveyed folds were growing. We then place the various identified fracture sets into a single stress field setting, perturbed by the leading NW-SE transverse lineaments that dominate this region.